The survival interactional strategies toward sustainable livelihoods amongst the migrants in the rural areas of Limpopo Province - Mabasa, M. A.; Makhubele, J. C.; Kwakwa, M. M.; Matlakala, F. K.; Mafa, P.; Baloyi, T. V.; Masilo, D. T.; Rabotata, N. E. (Technium Social Sciences Journal, 2021)
Survival interactional strategies are important for migrants towards sustainable livelihoods. The purpose of the study was to describe the survival interactional strategies toward sustainable livelihoods amongst the migrants in the selected areas of South Africa. This research was qualitative and used descriptive design to zoom into the survival interactional strategies toward sustainable livelihoods amongst the migrants. Researchers used purposive and convenient sampling techniques to sample the migrants’ youth. Data was collected through telephonic individual interviews to comply with COVID-19 national regulations and analyzed thematically. The study considered research ethics and trustworthiness as a research quality criteria. Findings showed that there is a need for effective social networks, sense of togetherness, entrepreneurial network, emotional support and economic support which are not easily realized by people from foreign countries as some of the South African policies are unfavorable to immigrants. Without those mentioned above, the immigrants face challenges when engaged with established relationship with people in the same business, support from spouses and fellow countrymen, functional reciprocal referral system, credit sales of goods, and teamwork as survival interactional strategies toward sustainable livelihoods amongst the immigrants. The survival interactional strategies are not easily realized by immigrants as some of the South African Policies and realities are unfavorable to the conditions of the people from the foreign countries. Social workers are thus, required to provide awareness on human diversity, and the impacts of xenophobic attacks to the South African community. Social work practitioners should also be mandated to develop and run an awareness programme on the survival interactional strategies toward sustainable livelihoods amongst the migrants.